The effectiveness of systemic enzyme therapy in complex treatment chronic pancreatitis in old age - Shevchenko, N. A.; Babinets, L. S. (Journal of Education, Health and Sport, 2021)
Relevance. The variety of functional changes in internal organs characteristicofgeriatricage necessitates the search for drugs that can exert a multifaceted effect on various links in the pathogenesis of chronic pancreatitis (CP) in comorbidity with the most common diseases of the elderly. Purpose. Investigation of the effectiveness of the inclusion of a systemic enzyme therapy drug in the complex treatment of chronic pancreatitis in elderly patients. Materials and methods. We examined 77 patients with CP over the age of 66 years, the average age (71.3 ± 1.4) g. Group I of patients with CP (23 patients) - took aconventional therapeutic complex (MC) for three months: pantoprazole 40 mg on an empty stomach according to requirement, continuous enzyme replacement therapy with pure pancreatin in an adequate dose with each meal, prokinetics / or antispasmodics if necessary. Group II consisted of 34 patients with CP (MC + W), in addition to LK, the drug of systemic enzyme therapy (SET) Wobenzym, 5 tablets, was taken. three times a day for three months. The control group consisted of 20 patients without signs of pathology of the digestive system. The parameters of lipid metabolism were determined by the enzymatic-colorimetric method. The assessment of the depth of exocrine pancreatic insufficiency (PI) was determined by the level of fecal α-elastase (FαE) by enzyme-linked immunosorbentassay using standard BIOSERVELASTASE 1-ELISA kits. Statistical analysis was performed using Excel and the statistical package Statistica v. 5.0. Results. Additional inclusion of the drug SET (Wobenzym) in the generally accepted MC promoted a significant improvement in lipid profile parameters in elderly patients with CP, as well as a reliable correction of the excretory function of the P by the level of FαE (from the level of moderate to mild insufficiency). Conclusions. 1) The inclusion of Wobenzym in the general treatment complex contributed toa decrease in the levels of TC, βLP, TG and LDLP by 15.4%, 19.8%, 32.0% and 33.9%, respectively (p <0.001), as well as an increase in the level of HDLP by 21.7% and a decrease in AF (by 41.3%) (p <0.001); 2) under the influence of treatment with the use of Wobenzym, a significant increase in the level of FαE (by 42.6%) was found relative to this indicator to treatment (p <0.001), which significantly exceeded the results (by 15.8%) in the MC group, which were not statistically significant (p> 0.05).